KANDUNGAN LOGAM BERATKADMIUM (Cd) DAN TIMBAL (Pb) PADA SEDIMEN, AIR DAN IKAN TEMBAKUL (Periophthalmus sp) DI PERAIRAN DUMAI - Siregar, Yusni Ikhwan (Jurnal Kajian Lingkungan, 2013)
This research was held on June to August 2012 and aims to analyze the content of heavy metals Cd and Pb in sediment, sea water and tembakul (Periophthalmus sp) in Dumai waters and to determine the correlation between the three. The method used was a survey method with 4 stations sampling were set by purposive with the inclusionof the sourceof pollutants. There was a difference between the content of Cd and Pb in sea water, sediment and tembakul (Periophthalmus sp), in which the heavy metal contentin the sea wateris lower than in sediment and fish. The highest content of Cd in sea water is in Stations1, 2 and 3, which .077mg/L. In the sediment, the highest contentis in Station 3, which is1.819Î¼g/g and the lowest at Station 4, which is 0.690Î¼g/g. Another case in Tembakul, the highest content of Cd is in Station 1, which is 0.447Î¼g/g. Pb content of sea water is highest at Station 2, which is 0.787mg/L and the lowest is on station 4, is equal to 0.370mg/L. The highest content of Pb in the sediment is at station 2, which is 33.221Î¼g/g and remained the lowest at Station 4 with Pb contents value of 19.018Î¼g/g. At tembakul (Periophthalmus sp), the highest Pb content is in Station 2, which is 4.976Î¼g/g and the lowest at Station 4, which is 2,555Î¼g/g. The content of Cd and Pb tembakul in Dumai waters under the in fluence of Cd and Pb content of water and sediment 54,2% increase in the content of Cd in sediments under the in fluence of the water content of Cd.62.5% Cd metal content in fish is in fluenced by the water content of Cd and 42.6% are in fluenced by the Cd conten to f the sediment. For Pb in sediments 60.4% in fluenced by the Pb content of the water. 68.1% Pb metal content in tembakul in fluenced by the water content of Pb and 65.9% under the influence of the Pb content of sediment. It means, if the content of heavy metals in water and sediment increases, it will give a negative impact to tembakul.Keyword: Heavy Metal, Dumai, Water, Sedimen, Tembakul